Phylogenomic Characterization of Lopma Virus and Praja Virus, Two Novel Rodent-Borne Arteriviruses - Vanmechelen, Bert; Zisi, Zafeiro; Gryseels, Sophie; Goüy de Bellocq, Joëlle; Vrancken, Bram; Lemey, Philippe; Maes, Piet; Bletsa, Magda (Viruses, 2021)
Recent years have witnessed the discovery of several new viruses belonging to the family Arteriviridae, expanding the known diversity and host range of this group of complex RNA viruses. Although the pathological relevance of these new viruses is not always clear, several well-studied members of the family Arteriviridae are known to be important animal pathogens. Here, we report the complete genome sequences of four new arterivirus variants, belonging to two putative novel species. These new arteriviruses were discovered in African rodents and were given the names Lopma virus and Praja virus. Their genomes follow the characteristic genome organization of all known arteriviruses, even though they are only distantly related to currently known rodent-borne arteriviruses. Phylogenetic analysis shows that Lopma virus clusters in the subfamily Variarterivirinae, while Praja virus clusters near members of the subfamily Heroarterivirinae: the yet undescribed forest pouched giant rat arterivirus and hedgehog arterivirus 1. A co-divergence analysis of rodent-borne arteriviruses confirms that they share similar phylogenetic patterns with their hosts, with only very few cases of host shifting events throughout their evolutionary history. Overall, the genomes described here and their unique clustering with other arteriviruses further illustrate the existence of multiple rodent-borne arterivirus lineages, expanding our knowledge of the evolutionary origin of these viruses.
Keywords: Animals; infekce RNA viry; host spectrum; Genome, Viral; biologická evoluce; rodent-borne arteriviruses; Whole Genome Sequencing; Rodentia; High-Throughput Nucleotide Sequencing; RNA Virus Infections; genom virový; Phylogeny; Africa South of the Sahara; cross-species transmission; virus evolution; Arteriviridae; sekvenování celého genomu; vysoce účinné nukleotidové sekvenování; subsaharská Afrika; hlodavci; zvířata; Biological Evolution; fylogeneze